A review on ultra‐small undoped MoS2 as advanced catalysts for renewable fuel production - Guoping Liu; Lingling Ding; Yuxuan Meng; Ahmad Ali; Guifu Zuo; Xianguang Meng; Kun Chang; Oi Lun Li; Jinhua Ye (Carbon Energy, 2024)
Abstract Molybdenum disulfide (MoS2) has garnered significant attention in the field of catalysis due to the high density of active sites in its unique two‐dimensional (2D) structure, which could be developed into numerous high‐performance catalysts. The synthesis of ultra‐small MoS2 particles (<10 nm) is highly desired in various experimental studies. The ultra‐small structure could often lead to a distinct S–Mo coordination state and nonstoichiometric composition in MoSx, minimizing in‐plane active sites of the 2D structure and making it probable to regulate the atomic and electronic structure of its intrinsic active sites on a large extent, especially in MoSx clusters. This article summarizes the recent progress of catalysis over ultra‐small undoped MoS2 particles for renewable fuel production. Through a systematic review of their synthesis, structural, and spectral characteristics, as well as the relationship between their catalytic performance and inherent defects, we aim to provide insights into catalysis over this matrix that may potentially enable advancement in the development of high‐performance MoS2‐based catalysts for sustainable energy generation in the future.